KARAKTERISTIK INDIVIDU, BEBAN KERJA DAN LINGKUNGAN KERJA PENGARUHNYA TERHADAP EFEKTIVITAS KERJA KARYAWAN - Sari, Hesti Novfita; Arini, Eti (Yayasan Insani Mandiri Santani, 2021)
This study aims to determine: (1) Individual Characteristics and its Effects on Employee Work Effectiveness at PT. Bengkulu Kokoh Perkasa (2) Workload and Its Effect on Employee Work Effectiveness at PT. Bengkulu Kokoh Perkasa (3) Work Environment and Its Effect on Employee Work Effectiveness at PT. Bengkulu Kokoh Perkasa (4) Individual Characteristics, Workload and Work Environment and their effects on Work Effectiveness of Employees at PT. Bengkulu Sturdy Perkasa. This research method is quantitative with a population of 110 individuals, while the sample was taken using the Slovin formula with an error rate of 10% so that the results obtained 52 respondents. The research data collection technique was carried out by observation and questionnaires. The research variables consist of Individual Characteristics (X1), Workload (X2), Work Environment (X3), and Employee Work Effectiveness (Y). The result of multiple linear equation is Y = 1.769 + 1.104 (X1) + 0.447 (X2) + 0.125 (X3). The results of testing of variable hypothesis Individual Characteristics (X1), Workload (X2), and Work Environment (X3), based on the results of the F test, it was obtained F sig 321,787 and a significance value (sig) of 0.000. This result means that the significance value is 0.000 <0.050, it means that H3 is accepted. This means that the individual characteristics variable, workload And the Work Environment simultaneously influences Work Effectiveness of Employees at PT. Bengkulu Sturdy Perkasa. The result of t count for the Individual Characteristics variable (X1) is 12,809 and the significant value (sig) 0,000 means 0,000 <0.050, the Workload variable (X2) is 5.043 and the significant value (sig) 0.000 means 0.000 <0.050 and the Work Environment variable (X3) is 2.479 and a significant value (sig) 0.017 means 0.017 <0.050, then the hypothesis Ha is accepted, in other words Individual Characteristics (X1), Workload (X2) and Work Environment (X3) have a significant effect on Employee Work Effectiveness at PT. Bengkulu Sturdy Perkasa.Keywords: Individual Characteristics, Workload, Work Environment and Employee Effectiveness.